Akmolla's Poetry in the Context of Interliterary Relations: Continuity of Kazakh and Bashkir Linguo-Poetic Traditions - Abylkasov, Garifolla; Shayakhimov, Daulet; Orazkhanova, Maigul; Kazhibayeva, Gulden; Smagulova, Nurgul; Osken, Assem (Forum for Linguistic Studies, 2025)
This study investigates the poetic heritage of Miftakhetdin Akmolla (1831–1895), an outstanding poet, educator, and thinker who occupies a central place in the cultural and literary history of both Kazakh and Bashkir peoples. The article examines Akmolla’s creative legacy as an interliterary phenomenon, revealing the linguistic, ideological, and poetic continuities that unite the two national literary traditions. Through a comparative linguo-poetic analysis of his poems in Kazakh and Bashkir, the research identifies the system of spiritual and ethical values that form the foundation of his worldview—faith (iman), knowledge (ghylym), morality (ädep), patience (sabyr), and struggle against the nafs. The paper also focuses on poetic devices such as metaphor, alliteration, repetition, and syntactic parallelism, which function as linguistic mechanisms for expressing his didactic and philosophical ideas. The analysis demonstrates that Akmolla's poetic discourse merges Enlightenment ideals with Islamic ethics and folk aesthetics, transforming poetry into a means of moral instruction and national self-awareness. His concept of the kämil adam (perfect person) synthesizes rational cognition and spiritual development, positioning man as a moral and intellectual center of the world. The findings reveal that Akmolla's works embody a model of intercultural dialogue within the Turkic literary space, integrating universal humanistic principles with distinctive linguistic imagery. The study contributes to the understanding of interliterary processes and linguistic-philosophical continuity in Turkic poetry, showing Akmolla's role as a bridge between cultures and as a unifying figure in the shared spiritual heritage of Turkic nations.